Managing Opioid Withdrawal for Hospital Patients in Custody. Issue 2 (March 2017) - Shi, Connie R.; Kandola, Manjinder S.; Tobey, Matthew; Singer, Elizabeth
Abstract: Dr. Brown, a hospitalist, admits Mark, a patient transferred from a local jail for management of cellulitis. The patient, who was taken into custody two days prior to hospital admission, has a history of intravenous heroin use. Mark explains that he had been prescribed buprenorphine‐naloxone maintenance therapy for opioid use disorder for several years prior to being arrested and had not used other opioids during that time. As a policy, the jail where Mark is detained does not prescribe opioid agonists, and his maintenance therapy was stopped upon his arrival there. Dr. Brown discovers that Mark is diaphoretic and appears distressed. Mark's symptoms suggest to Dr. Brown that, in addition to having cellulitis, Mark is actively withdrawing from opioids. Mark tells Dr. Brown that he has felt "horrible" since his buprenorphine‐naloxone therapy was stopped and that he now has intense cravings for opioids. He asks Dr. Brown to help alleviate the withdrawal symptoms. Dr. Brown, who is accustomed to treating opioid withdrawal with opioid replacement therapy, wonders if she should initiate ORT for Mark while he is in the hospital.